Examining Factors Driving University Students’ Transition to Online Purchasing During the Post-Pandemic Era: A Case Study on Double-Double Sales - Karen, Chong Kah Yee; Xu, Cheah Shu (Universitas Muhammadiyah Sidoarjo, 2024)
The COVID-19 pandemic had a tremendous impact on customer behavior, specifically among university students, initiating a move towards online purchases. This change has affected traditional retail sectors and resulted in new e-commerce trends. Before the outbreak of COVID-19, people were accustomed to purchasing goods physically. Consequently, many organisations have adopted various marketing strategies to entice customers. One such tactic frequently employed by e-commerce organizations is the “Double-Double” sale. The objective was to identify key factors prompting students to engage in online shopping. To comprehend the factors motivating Malaysians, particularly university students, to participate in online shopping during Double-Double sales, this study conducted semi-structured interviews with 13 Malaysian university students. The findings revealed that convenience, pricing, and social media advertisements are key drivers of Malaysian university students’ shift from traditional to online shopping.